EFFECTS OF BUSERELIN ACETATE ON CONCEPTION RATE IN REPEAT BREEDING DAIRY CATTLE - HAILU, BIRHANU; GEBREKIDAN, BERIHU; ALEMAYEHU, GEZAHIGN; TEKLU, TESHALE (The Indian Journal of Animal Reproduction, 2023)
The aim of the present study was to evaluate the effect buserelin acetate given 12 days post Al and double inseminations during estrus period of dairy cattle on improvement of conception rate. Field trial was carried out on repeat breeding cross breed dairy cows which are lactating and apparently healthy that exhibits estrus regularly. A total of forty four repeat-breeding cows from twenty herds were selected and assigned randomly in to two equal groups, A and B: one treated and one control group. Group A (n=22) cattle were treated intramuscularly with 10 μg buserelin acetate 12 days post Al. Group B (n=22) cattle were inseminated once during estrus exhibition with single service and considered as control. Dairy cows were examined for pregnancy after three months through rectal palpation. Pregnancy rates recorded were 55%, and 32% in A and B respectively. The conception rates of treated group exceed control group by 23% respectively. Treated group showed a significant statistical variation (P<0.05) as compared to control groups. It is recommended that the use of GnRH injection 12 days post Al and can improve pregnancy rate in repeat breeding cross bred dairy cows.